Status of Man, Biology and Theology - Muhammad Abid Nadeem (jihat-ul-islam, 2021)
Man's instinct has instigated him to assess the status of this world and the creatures therein. This desire of man has led him to raise questions on his own status in this world. Various branches of knowledge, philosophy, psychology, anthropology and biology etc. discuss this problem of man. Modern biological knowledge has reduced man's status to an animal being. This is in contradiction to anthropological studies and theology. Theological knowledge raises man's status to the vicegerent of God; manipulator manager and organizer of there worldly resources. There are many distinctions that are the proof of his dignity.